Utilization of Rhizoplane Bacteria and Arbuscular Fungi Mycorrhizal (AFM) to Improve Growth of Jelutong Seedling (Dyera polyphylla Miq. Steenis. - Irnayuli R. Sitepu; Irdika Mansur; Rifa’ Atunnisa (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2010)
Nontimber forest products (NTFPs) represent sources of income from tropical forest, but some NTFP species have decreased in population and become endangered due to overexploitation. There is increasing concern that the planting stock of Dyera polyphylla is not sufficient to sustain the yield of NFTPs. The beneficial root colonizing rhizosphere bacteria, the so-called plant growth-promoting rhizobacteria have been known to carry out many important ecosystem processes, such as those involved in the nutrient cycling and/or seedling establishment. The roots of most plant species associate with certain soil fungi and establish what are known as mycorrhiza. The objective of this study was to determine the effect of two arbuscular miycorrhizal (AMF) fungi, Glomus sp., Gigaspora sp. and thirteen strains of hizoplane bacteria (CK32, FL.13.2.1, JW1, JW6, JW9, JW13, JW14, CK26, CK4, JW3a, SB, NT, CR.R1), on the early growth of D. polyphylla, under greenhouse condition. Percentage of AMF colonization, plant growth, and nitrogen (N) and phosphorus (P) concentration were measured after 150 days of planting. The results showed that the percentage of AM colonization of D. polyphylla was 100%. Colonization by Glomus sp. significanly increased plant height by 18,95% and diameter by 16,16% compared to those non AMF. Combination of bacterial and AMF inoculant between JW13 and Glomus sp. increased shoot weight by as much as 36,28% from control and increased N concentration by 69,59% compared to those of non inoculate a seedlings. Combination of JW1 and Gigaspora sp. increased P concentration by as much as 42,05% compared to those of non inoculate seedlings. Despite the difficulty of selecting a multifunctional microbial consortia, appropriate microbial combinations can be recommended for a biotechnological input related to improvement of plant performance.